Climate change and agriculture in South Asia: adaptation options in smallholder production systems - CGIAR Research Program on Wheat (2019)
peer reviewed journal article presents a systematic review of the impacts of climate change on crop production and also the major options in the agricultural sector that are available for adaptation to climate change.